The Effect of Time Management on the Academic Achievement of Students Working in Tana Toraja Regency - Nurlela; Chrismesi Pagiu; Rati Pundissing (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of time management on the academic achievement of students who work in Tana Toraja Regency. This study uses a quantitative approach with a simple regression analysis method. The population in this study is the number of students who work while studying in Tana Toraja Regency, with the sampling technique using the lemeshow formula with a maximum estimate of 5%. Data were collected through questionnaires distributed to respondents and analyzed using SPSS Version 23 data processing. The results of the study indicate that time management has a positive and significant effect on the academic achievement of students who work with the results of the t-test calculation on the time management variable t count> t table with a value of 11.267> 1.985. This means that the better the student's ability to manage time, the higher the academic achievement achieved.